Smart parking system for green computing - Atiqur Rahman (Penerbit Universiti Kebangsaan Malaysia, 2023)
A “smart city” is one that makes use of info and comm technologies (ICTs) to increase the awareness, interaction, and effectiveness of city services and monitoring. It might be smart technology, smart design, smart mobility, smart utilities, smart housing, smart healthcare, smart transportation, smart lighting, smart phone detection, smart road, smart traffic management, and smart parking etc. The solicitation of smart cities will increase unexpectedly with the rapid increase in IoT infrastructure. Smart city idea notably going up to city lifecycle. The focal point of this paper is to present an intelligent parking system consuming a novel iOS app-based implementation for smart cities’ demands, which permits a driver to determine a parking lot and a vacant slot in that lot indoor a municipality. This paper additionally focuses on reducing the searching time for determining the parking lot using our proposed method, namely, the booking method. This, in short, lessens the gasoline deployment which in turn cuts carbon trails in the weather, as a way of life, additionally averting useless traveling via packed parking lots in a parking lot that can be useful in decreasing illegal parking and in a way help with the traffic jams we see in our city.